2018
DOI: 10.1016/j.jastp.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale magnetic fields and anomalies of chemical composition of stellar coronae

Abstract: We present evidence that anomalies in abundance of the chemical admixtures with the low first ionization potential (FIP) in the low corona of the late-type stars can be related to a topology of the large-scale magnetic field. Observational data from Ulysses and the Stanford Solar Observatory reveal the high correlations between the FIP effect of the solar wind and amount of the open magnetic flux. To analyze the stellar activity data we relate the amount of the open magnetic flux with the ratio between poloida… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…Over solar cycle time scales, Brooks et al (2017) showed a strong correlation of Ne coronal to photospheric abundance ratios, to the phases of the solar cycle. Pipin and Tomozov (2018) further extended this to stars and have shown that the FIP bias variations are likely related to the large scale coronal magnetic field and activity level of the toroidal magnetic field. Such variations could also occur at shorter time scales and smaller spatial scales.…”
Section: Introductionmentioning
confidence: 87%
“…Over solar cycle time scales, Brooks et al (2017) showed a strong correlation of Ne coronal to photospheric abundance ratios, to the phases of the solar cycle. Pipin and Tomozov (2018) further extended this to stars and have shown that the FIP bias variations are likely related to the large scale coronal magnetic field and activity level of the toroidal magnetic field. Such variations could also occur at shorter time scales and smaller spatial scales.…”
Section: Introductionmentioning
confidence: 87%